1992
DOI: 10.1002/abio.370120602
|View full text |Cite
|
Sign up to set email alerts
|

Multiple shoot formation and phenotypic changes of R0 regenerants in Hypericum perforatum L.

Abstract: Seedlings of Hypericum perfaroturn L. have produced multiple shoots on RM medium supplemented with 2.22 or 4.40pM BAP. Regenerants were evaluated for variability in several morphological characteristics. A comparison with the control showed significant differences in fresh and dry matter and height of plants, but did not effect branching and the number of glands containing dianthrones.Seeds of Hypericumperforatwn L. (Hypericaceae), cv. Topas were surface sterilized with 5% Chloramine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…The formation of both shoots and roots on the same medium eliminates one step of medium transfer in the propagation of this species, thus reducing the total time and cost required for plant regeneration. Similar results were reported for H. perforatum (Cellá rová et al 1992;McCoy and Camper 2002) and H. brasiliense (Cardoso and Oliveira 1996).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The formation of both shoots and roots on the same medium eliminates one step of medium transfer in the propagation of this species, thus reducing the total time and cost required for plant regeneration. Similar results were reported for H. perforatum (Cellá rová et al 1992;McCoy and Camper 2002) and H. brasiliense (Cardoso and Oliveira 1996).…”
Section: Resultssupporting
confidence: 93%
“…Explants cultured on control medium without growth regulators did not respond satisfactorily. Similar effect of BAP on shoot development in H. perforatum and H. foliosum has been reported previously (Cellá rová et al 1992;Moura 1998). The absence of rooting in the presence of NAA, as mentioned by the same studies, was also confirmed for H. polyanthemum.…”
Section: Resultssupporting
confidence: 84%
“…As a result, many investigators have discussed how one might obtain H. perforatum shootlet meristem cultures in vitro from which hypericins and hyperforin can be detected [10,47,66,68,86,87]. Callus and cell‐suspension cultures of H. perforatum are usually established from the shoots of surface‐sterilized seeds that germinate in culture.…”
Section: Challenges and Strategies To Enhance Production Of Hypericinmentioning
confidence: 99%
“…Having more leaf surface in comparison with stem tissue in the sample would shift the proportion of hypericin recovered, since the glands containing hypericin are generally located along the leaf margins. Cellárová et al [66] demonstrated that several morphological characteristics of H. perforatum cv. 'Topas' regenerants varied considerably without a clear trend when grown on media with a range of kinetin concentrations.…”
Section: Genetic and Environmental Effects On Secondary Metabolismmentioning
confidence: 99%
“…Such universal type medium can be a good choice for large-scale continuous biomass production systems. Shoot cultures of H. perforatum require exogenous cytokinins alone or in combination with auxins for good growth and multiplication (Čellárová et al 1992, Zdunek and Alfermann 1992, Murch et al 2000. Proper cytokinin/auxin balances is also required for the establishment and shoot regeneration of H. perforatum callus tissues (Čellárová et al 1995, Preto andSantarém 2000).…”
mentioning
confidence: 98%